1998
DOI: 10.1074/jbc.273.36.23176
|View full text |Cite
|
Sign up to set email alerts
|

Role of MutS ATPase Activity in MutS,L-dependent Block of in Vitro Strand Transfer

Abstract: In addition to mismatch recognition, Escherichia coliMutS has an associated ATPase activity that is fundamental to repair. Hence, we have characterized two MutS mutant gene products to define the role of ATP hydrolysis in homeologous recombination. These mutants, denoted In addition to its role in replication fidelity, mismatch repair contributes to genome stability by controlling the level of recombination between closely related sequences (1-9). In Escherichia coli, MutS and MutL act to block recombinant yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 42 publications
4
50
2
Order By: Relevance
“…This ATP binding requirement likely is not caused solely by MutS for the following reason. The K m for ATP hydrolysis catalyzed by our purified MutS preparation was 23 M (data not shown), consistent with a recent report (26). The K m for ATP during the overall mismatch repair reaction in E. coli is approximately 300 M (4).…”
Section: Discussionsupporting
confidence: 77%
“…This ATP binding requirement likely is not caused solely by MutS for the following reason. The K m for ATP hydrolysis catalyzed by our purified MutS preparation was 23 M (data not shown), consistent with a recent report (26). The K m for ATP during the overall mismatch repair reaction in E. coli is approximately 300 M (4).…”
Section: Discussionsupporting
confidence: 77%
“…Such extensions are catalyzed by RecA and facilitated by RuvAB to cover stretches that are 1 kbp or more long (1,33). MutS was shown to impede strand exchange and branch migration between divergent DNA sequences by RecA (87,88). Similarly, branch migration through regions of heterology stimulated by RuvAB was prevented through the MutSL complex (21).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the sexual isolation of strains defective in mismatch repair is decreased (13,46). The antirecombination effect of the MMR system seen in vivo was explained by the abortion of strand exchange reactions with MutS and MutL demonstrated in vitro (87,88). Therefore, the MMR system controls not only the level of spontaneous mutability of cells but also the level of recombinative acquisition of new genetic information by homologous recombination (9,81).…”
mentioning
confidence: 99%
“…Our current work does not directly address the role of MMR in hDNA rejection, but our experiments with pHYB121 led us to conclude that rapid action of MMR on mismatches in hDNA is not a suitable explanation for dismantling hDNA. It has been shown that MMR in bacteria reduces the rate of strand exchange in the presence of mismatches (Worth et al 1994(Worth et al , 1998Bazemore et al 1997;Zahrt and Maloy 1997;Fabisiewicz and Worth 2001) but, importantly, MMR does not target preformed mismatched hDNA (Worth et al 1994;Westmoreland et al 1997). Work done in yeast also provides evidence that MMR proteins play a role in impeding branch migration through mismatches Jinks-Robertson 1998, 1999).…”
Section: Discussionmentioning
confidence: 99%